Pediatric oncological spondylolisthesis: the contribution of Physical Medicine and Rehabilitation and Orthodontics. A narrative review - Andrea Scribante; Matteo Pellegrini; Martina Ghizzoni; Maria Gloria Nardi; Barbara Rocca; Marco Monticone (Hygeia Press di Corridori Marinella, 2023)
Different forms of spondylolisthesis (SP) have been described. This pathological condition is often due to a birth defect in the lumbar area, but it can also be caused by a sudden injury resulting from an acute trauma. In athletic children and adolescents, SP may represent a stress fracture triggered by overuse. SP can also be consequent to cancer, although this clinical condition is rare. The first manifestation of SP is pain. Neoplasm-related SP may also induce physical impairment and postural alterations of the spine, such as flatback and hyperkyphosis. These changes may also affect the entire spine, including the cervical region (i.e., forward neck) and the head (i.e., forward head). A prompt assessment of children with oncological SP is crucial and involves clinical and radiological evaluations. Multiple healthcare professionals are involved in the management of children with oncological SP, including spinal specialists, pediatricians, oncologists, and psychologists. Orthodontists may also contribute to cervical posture evaluation. The authors of this review aim to provide a comprehensive overview of the topic, particularly focusing on the clinical assessment of children with oncological SP and the possibilities for rehabilitative treatment.